Associations Between Safety of Certolizumab Pegol, Disease Activity, and Patient Characteristics, Including Corticosteroid Use and Body Mass Index - Vivian P. Bykerk (ACR Open Rheumatology, 2021)
Objective To investigate the impact of baseline and time‐varying factors on the risk of serious adverse events (SAEs) in patients during long‐term certolizumab pegol (CZP) treatment. Methods Safety data were pooled across 34 CZP clinical trials in rheumatoid arthritis (RA), axial spondyloarthritis (axSpA), psoriatic arthritis (PsA), and plaque psoriasis (PSO). Cox proportional hazards modeling was used to investigate the association of baseline patient characteristics with risk of serious infectious events (SIEs), malignancies, and major adverse cardiac events (MACEs). Cox modeling for recurrent events assessed the impact of time‐varying body mass index (BMI), systemic corticosteroid (CS) use, and disease activity on SIE risk in RA and SAE risk in PSO. Results Data were pooled from 8747 CZP‐treated patients across indications. Cox models reported a 44% increase in SIE risk associated with a baseline BMI of 35 kg/m2 or more versus a baseline BMI of 18.5 kg/m2 to less than 25 kg/m2. Baseline systemic CS use, age of 65 years or more, and disease duration of 10 years or longer also increased SIE risk. Older age was the only identified risk factor for malignancies. The risk of MACEs increased 107% for BMI of 35 kg/m2 or more versus BMI of 18.5 kg/m2 to less than 25 kg/m2 and increased 51% for men versus women. Higher disease activity, older age, systemic CS use, BMI of 35 kg/m2 or more, and baseline comorbidities were SIE risk factors in RA. Age and systemic CS use were risk factors for SAEs in PSO. Conclusion Age, BMI, systemic CS use, and disease activity were identified as SIE risk factors in CZP‐treated patients. Risk of malignancies was greater in older patients, whereas obesity and male sex were MACE risk factors.